MOTIVASI INTERNAL PERAWAT DALAM MENERAPKAN SASARAN KESELAMATAN PASIEN (SKP) 5 - Meri Oktariani; Verily Wicaksana; Dzurriyatun Thoyyibah ZA (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2021)
Patient safety is a system where the hospital makes patient care safe. There are six goals for patient safety. Patient Safety Goal (PSGs) 5 is to reduce the risk of infection related to health services. An effort to eliminate the problem of infection by maintaining cleanliness through handwashing. One of the factors that influence nurses to implement PSGs 5 is internal motivation. The purpose of this study was to identify the relationship between the nurses' internal motivation and the implementation of Patient Safety Goals (PSGs) 5 in the inpatient room at Simo Hospital of Boyolali. This study used a descriptive correlative method with a cross-sectional study approach. A total sampling technique was applied to determine its samples consisted of 42 respondents. The data collection instruments were the internal motivation questionnaire and the patient safety goals (PSGs) 5 observation sheet. Its data were examined by using the Rank Spearman correlative test. The results showed a p-value of 0.000 <0.05. Therefore, Ho was rejected, Ha was accepted, and r was 0.730. These results indicate a high relationship, have a positive and unidirectional correlation where the higher the internal motivation, the higher application of patient safety goals (PSGs) 5. This study infers that there is a relationship between nurses' internal motivation and the application of patient safety goals (PSGs) 5 in the inpatient room at Simo Hospital of Boyolali.